The Influence of Life Expectancy Rate And Old School Rate To GRDP Percapita and Economic Growth In Central Kalimantan Province 2011-2015 - HEPI HEPI; WIWIN ZAKIAH (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2018)
ABSTRACT The aims ofstudy is to analyze how much influence Life Expectancy Rate, School Average Average to GDRP per capita and Economic Growth. The data used in this research is secondary data from Central Bureau of Statistics of Central Kalimantan Province. While the analytical method used is to use path analysis (Path Analysis) assisted SPSS software version 22.0. The results showed that life expectancy had positive but not significant effect to GDRP per capita. The average length of school has a positive and significant impact on GDRP per capita. Life expectancy has negative but insignificant effect on economic growth. The average length of school has a positive and significant impact on economic growth. GDRP per capita has a positive and significant impact on economic growth. Life expectancy has no significant effect on economic growth through GDRP per capita. The average length of school has no significant effect on economic growth through GDRP per capita